1998
DOI: 10.1111/j.2042-3306.1998.tb04528.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐articular pressure, elastance and range of motion in healthy and injured racehorse metacarpophalangeal joints

Abstract: The objective of this study was to determine if intraarticular pressure, elastance of the soft tissue forming the dorsal pouch, and range of motion in flexion measurements are significantly different in Thoroughbred metacarpophalangeal joints with clinical evidence of idiopathic synovitis, primary synovitis, synovitis/ capsulitis, or osteoarthritis relative to clinically normal joints. Forty-two metacarpophalangeal joints, in 25 active or retired Thoroughbred racehorses, were categorised by palpation and visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 21 publications
3
31
1
2
Order By: Relevance
“…This may be related to the high force (200 N) that was applied during this experiment. Studies have shown that the flexion test induces an increased intra‐articular pressure of the metacarpophalangeal joint and increased intraosseous pressure (Stolk and Firth 1994; Strand et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the high force (200 N) that was applied during this experiment. Studies have shown that the flexion test induces an increased intra‐articular pressure of the metacarpophalangeal joint and increased intraosseous pressure (Stolk and Firth 1994; Strand et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…38 Peak reduc- tion in range of motion, corresponding to increased joint pain, was evident 12 hours after the first LPS injection. 38 Peak reduc- tion in range of motion, corresponding to increased joint pain, was evident 12 hours after the first LPS injection.…”
Section: Discussionmentioning
confidence: 99%
“…35 A handheld goniometer g was positioned so that the center of the rotation was over the center of rotation of the MCP joint. 38,39 Synovial fluid analysis-Two to 6 mL of synovial fluid was collected from MCP joints into EDTA and heparinized tubes. 37 Metacarpophalangeal joint swelling (edema score and joint circumference)-Forelimbs were palpated by 2 investigators (DMB and ALB), who were unaware of the treatment horses had received.…”
Section: Evaluation Of Pain-free Range Of Joint Motion-mentioning
confidence: 99%
“…Joint pain is thought to be related to increasing tension and pressure on structures located on the extension and flexion sides of the joint, respectively (Verschooten and Verbeeck 1997), increased intraarticular pressure (IAP) (Stolk and Firth 1994) and/or intra-osseous pressure (IOP) (Strand et al 1998). Therefore, the conclusion seems warranted that a positive flexion test in a clinically sound horse is probably caused by pain originating from the MCP joint and related structures.…”
Section: Discussionmentioning
confidence: 99%
“…Joint pain is thought to be related to increasing tension and pressure on structures located on the extension and flexion sides of the joint, respectively (Verschooten and Verbeeck 1997), increased intraarticular pressure (IAP) (Stolk and Firth 1994) and/or intra-osseous pressure (IOP) (Strand et al 1998). In fact, this is one of the suggested mechanisms through which joint disorders are thought to lead to an increase in response to the flexion test (Strand et al 1998). Mechanoreceptors located in the joint capsules react promptly to the nonphysiological loading during the flexion test.…”
Section: Discussionmentioning
confidence: 99%